Commentary: Essential Programs and Services Model - Gallaudet, Denison; Sciopone, Henry; Scott, Thomas; Kautz, Robert; Shaw, Roger; Eastman, Mark; Lyons, Richard; Hasson, Bob (Maine Policy Review, 2001)
To further discussion about the Essential Programs and Services (EPS) model for funding public education in Maine, Maine Policy Review asked eight superintendents—representing districts across the state— to provide their views. We also asked each to discuss the needs of his district and whether additional state policy options were necessary to tackle the most pressing issues. The districts represented by these superintendents are a cross section of urban and rural high-receivers and low-receivers. Still, several commonalities emerge: the need for a state commitment that does not wax and wane with the business cycle; the urgency of professional development for new and experienced teachers; and, the importance of linking student outcomes with student assessment measures and student funding. In short, EPS is not seen as a solution to the state’s ongoing debate over public-education funding, but is recognized as a necessary first step.
Keywords: Maine school funding; essential programs and services; EPS